Theoretical Basis of Improving the Methodology of Developing the Creative Competence of Future Specialists in Preschool Educational Organizations - Saydullaeva Nargis Ilhom qizi (Researchparks Publishing, 2021)
This article describes the creative qualities of future professionals in preschool education, the theoretical basis for improving the methodology of developing creative competence.